Occupational Safety and Health from The Perspective of The ISO 26000 standard - Ewa MAZUR-WIERZBICKA (Communications of International Proceedings, 2021)
The aim of this paper is to identify and assess the status of safety and health at work in the concept of corporate social responsibility with particular emphasis on its place in the ISO 26000 standard. First, the paper depicts health and safety at work as an integral part of corporate social responsibility; second, light is shed on the ISO 26000 standard; third, the place of occupational health and safety in the ISO 26000 standard is identified. Such a structure allowed the implementation of the pursued aim. This study is based on relevant literature and RBF reports.
Keywords: Occupational Health And Safety; Occupational Health And Safety Management; Social Corporate Responsibility; Norm ISO 26000.